Upaya Guru dalam Menanamkan Nilai Kejujuran pada Anak Usia Dini melalui Bermain Peran di KB Madani Mandailing Natal - Lisnawati; Mhd. Habibu Rahman (Education & Learning, 2025)
This study aims to describe teachers' efforts to instill the value of honesty in early childhood through role-playing at the Madani Mandailing Natal Kindergarten. The method used was a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results showed that teachers employed various strategies, such as designing role-play scenarios containing the value of honesty, providing positive reinforcement, guiding children's reflection after play, creating a supportive learning environment, and integrating the value of honesty into daily activities. Through these activities, children began to demonstrate behavioral changes toward greater honesty, such as telling the truth, admitting mistakes, and not taking others' rights. The conclusion of this study is that role-playing is an effective method for teaching the value of honesty to early childhood when implemented consistently and creatively.